Why Kant’s Hope Took a Historical Turn in Practical Philosophy - Woo, Jaeha (Con-Textos Kantianos. International Journal of Philosophy, 2023)
In the beginning of his critical period, Kant treated the perfect attainment of the highest good—the unconditioned totality of ends which would uphold the perfect proportionality between moral virtue and happiness—as both the ground of hope for deserved happiness and the final end of our moral life. But I argue that Kant moved in the direction of de-emphasizing the latter aspect of the highest good, not because it is inappropriate or impossible for us to promote this ideal, but because the endless pursuit of it offers no prospect of moral satisfaction. I take this change as one possible reason for him to shift his focus more toward social and political progress in history, which has as its main subject the human species which is in some sense immortal.